Character Segmentation to the Case Study Image of Quadratic Equation Expression - Pradnyawati, Putu Indah; Arta Wibawa, I Gede (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
The introduction of digital mathematical expressions can be said to be unusual because mathematical expressions consist of various symbols. The introduction of mathematical expressions can be divided into two main steps, namely the introduction of symbols and structural analysis. Segmentation of an image is an important part in the recognition of handwritten mathematical expressions, because segmentation is the first step of the recognition process. In this study, we will present the process of handwriting image segmentation for mathematical expressions in the form of quadratic equations using the Connected Component Labeling (CCL) method. From the results of the research conducted, it can be concluded that the segmentation process has succeeded in segmenting the handwritten images of mathematical expressions in the form of quadratic equations by producing the characters (compound characters) that make up mathematical expressions and grouping the ranks and basic numbers of quadratic equations.